NATIVE AND NON-NATIVE ENGLISH SPEAKING TEACHERS: PESANTREN STUDENTS’ PERCEPTIONS IN INDONESIA - Imra'atus Shalihah (Graduate Program, University of Islam Malang, 2021)
AbstractThe findings of a study on pesantren students' attitudes toward native and non-native English-speaking teachers (NEST and NNEST) in Indonesia are presented in this paper. Interviews with ten students from one of the secondary schools in a pesantren in Jember, East Java, Indonesia were used to gather qualitative data. The results of this study revealed that the participants were aware of the advantages and disadvantages of NEST and NNESTs. The advantages that students perceived about learning English with NEST include oral skills such as speaking, pronunciation, and enriching new vocabularies. In addition, students could also learn new culture from NEST, and it made students feel motivated and wanted to study English more deeply. The study, on the other hand, revealed a number of NEST disadvantages related to grammar explanation. While in the cultural aspect, most students did not like NEST because of different culture and religion. Consequently, some students felt unmotivated to learn English with NEST. About the advantages and disadvantages of learning English with NNEST, the findings indicated that the advantages of learning with NNEST were that NNEST could provide clear grammar explanation and understand the needs and learning difficulties of students, so that the students felt comfortable in asking something they did not understand to NNEST. Moreover, they felt comfortable because of having the same culture, religion, habits, and appearance. As a result, they thought that learning English with NNEST increased their motivation. The disadvantages of NNESTs, on the other hand, as seen by students, were poor pronunciation and a lack of vocabularies. Furthermore, students could not learn or share new culture. Consequently, their insights and experiences did not increase.